Cultural integration in MERCOSUR - Ramos, José Onesio (1999)
The purpose of this article is to present some reflections about the importance of cultural integration in Mercosur, since there seems to be a wide discussion about integration in the economic, legal and commercial aspects, leaving the cultural aspect in the background. The speeches of the President and the Minister of Foreign Affairs of Brazil, from 1995 to 1998, will be analyzed in order to understand the attention paid by these authorities to cultural integration in Mercosur.